2020
DOI: 10.1111/1759-7714.13591
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of clinicopathological characteristics and prognosis between combined and pure small cell lung cancer (SCLC) after surgical resection

Abstract: Background: Histologically, SCLC are classified as pure (P-SCLC) and combined subtypes (C-SCLC). Currently, few studies compare the clinicopathological characteristics and explore the treatment strategies applied to them. Methods: Between July 2005 and April 2016, the clinical records of 297 postoperative patients with pathologically confirmed SCLC were retrospectively analyzed. Kaplan-Meier method and Cox regression model were separately used for stratified univariate and multivariate survival analysis. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 21 publications
(54 reference statements)
1
27
0
Order By: Relevance
“…However, our figure was obviously larger than the figure of 28% found in a previous study (4). Notably, there were no statistical differences in relation to the clinical characteristics of the p-SCLC and c-SCLC groups, which supports the findings of Guo's and Zhang's previous research (13,14). In relation to the survival outcomes, Zhang's research revealed that c-SCLC patients had a worse OS rate than that of p-SCLC patients (14).…”
Section: Discussionsupporting
confidence: 78%
“…However, our figure was obviously larger than the figure of 28% found in a previous study (4). Notably, there were no statistical differences in relation to the clinical characteristics of the p-SCLC and c-SCLC groups, which supports the findings of Guo's and Zhang's previous research (13,14). In relation to the survival outcomes, Zhang's research revealed that c-SCLC patients had a worse OS rate than that of p-SCLC patients (14).…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, we found that patients can benefit from surgery and chemotherapy. Previous studies had proposed some factors that were potentially correlated with OS of C-SCLC, including smoking history, 10 extensive-stage disease, 11 lymph node metastasis, 2 , 8 adjuvant treatment, 2 , 10 , 11 and pathologically combined LCNEC 10 and SCC. 17 Lei et al reported that lymph node metastasis was significantly correlated with decreased disease-free survival (DFS) and OS in surgically resected C-SCLC, consistent with our finding.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Previous studies have shown that the clinical characteristics of C-SCLC do not differ significantly from those in patients with P-SCLC. [5,7,8] In addition, C-SCLCs have been treated based on SCLC guidelines, [9] similarly with a platinum agent and etoposide with or without thoracic radiation, after adjustments for tumor extent or stage for over three decades. [10] Therefore, to date, SCLC has been regarded as a 'homogenous' disease with little documented inter-tumor heterogeneity with respect to histology or molecular biology in clinical practice.…”
Section: Introductionmentioning
confidence: 99%